Faktor-faktor yang berhubungan dengan praktik pemberian ASI eksklusif pada bayi usia 0-6 bulan di Kabupaten Timor Tengah Selatan - Ari Tri Astuti; Hamam Hadi; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2019)
Factors associated with exclusive breastfeeding practice among infants aged 0-6 months in Timor Tengah Selatan DistrictBackground: The health profile of Indonesia in 2018 indicated only  68,74% of infants were exclusively breastfed. East Nusa Tenggara is one of the provinces with lower exclusive breastfeeding coverage than national data in 2018 with only 52,67%. A survey in Timor Tengah Selatan district showed that exclusive breastfeeding also decreased from 2015 and 2016 which was 63.3% to 59.1%. Several factors have been known to be associated with exclusive breastfeeding practice, such as mother’s education and occupation, household expenditure, antenatal care history, and husband’s support.Objective: To identify factors associated with exclusive breastfeeding practice among infants aged 0-6 months in Timor Selatan District, East Nusa Tenggara province.Methods: An observational study with a cross-sectional design was conducted among 155 lactating mothers of infants aged 0-6 months. The secondary data from "Study on behavioral analysis and food consumption/dietary practices among children under five, elementary school-age children, pregnant and lactating mother in Timor Tengah Selatan District of East Nusa Tenggara Province” were used. Raw data were collected in July 2012 in Amanuban Barat and Kie subdistrict, Timor Tengah Selatan. The data were analyzed in July-December 2014 using Chi-Square and logistic regression test. Results: Household expenditure, antenatal care location, and subdistrict associated with exclusive breastfeeding practice (p<0.05). Lactating mothers who did prenatal care at primary health care/primary health care satellite/hospital were 3.51 times more likely to breastfeed exclusively (OR=3.51; 95%CI: 1.03-11.9). Household expenditure (OR=0.27; 95%CI: 0.09-0.84) and subdistrict (OR=0.19; 95%CI: 0.05-0.71) had protective effect.Conclusions: A significant association was found between exclusive breastfeeding practice and household expenditure, antenatal care location, and the subdistrict in Timor Tengah Selatan district.